A Comparative And Statistical Approach To Leverage Cloud Computing And Big Data Analytics In E-Governance - Jadhav, Bhushan; Patankar, Archana B (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, the governments across the world uses internet for providing their maximum number of services to the different stakeholders with the help of ICT. But due to the legacy computing architecture and data processing technologies, it become difficult for the governments to fulfill the current requirement of E-governance which makes impact on its usage. Therefore the emerging technologies like cloud computing and big data analytics can be used together in E-governance to overcome the existing challenges related to computing and data processing. The Cloud computing and big data analytics can be used together to introduce the many features which are not there in existing system. But before opting them their relevance needs to be studied. Therefore the main objective of this paper is to perform the in-depth study of Cloud and Bigdata enabled E-governance along with the statistical and comparative analysis. This research paper also proposes a model for integrating cloud computing and big data analytics in to E-governance along with advantages and disadvantages